Sustainability of life cycle management for nuclear cementation-based technologies - Rahman, Rehab O. Abdel; Ojovan, Michael I. (Woodhead Publishing in energy., 2021)
Sustainability of Life Cycle Management for Nuclear Cementation-Based Technologies, edited by Dr. Rahman and Dr. Ojovan, presents the latest knowledge and research on the management of cementitious systems within nuclear power plants. The book covers aging, development and updates on regulatory frameworks on a global scale, the development of cementitious systems for the immobilization of problematic wastes, and the decommissioning and decontamination of complex cementitious systems. The book's editors and their team of experts combine their practical knowledge to provide the reader with a thorough understanding on the sustainability of lifecycle management of cementitious systems within the nuclear industry. Sections provide a comparative tool that presents national regulations concerning cementitious systems within nuclear power plants, check international and national evaluation results of the sustainability of different systems, help in the development of performance test procedures, and provide a guide on aging nuclear power plants and the long-term behavior of these systems in active and passive safety environments.